Starshades as technosignatures in direct imaging phase curves: application to the Habitable Worlds Observatory targets - Skoglund, Claudia I.; Mustill, Alexander J. ; 0000-0002-2086-3642 (Monthly Notices of the Royal Astronomical Society, 2025)
A star’s luminosity increases as it evolves along the main sequence (MS), which inevitably results in a higher surface temperature for planets in orbit around the star. Technologically advanced civilizations may tackle this issue by installing artificial structures – starshades – which can reduce the radiation received by the planet. Starshades, if they exist, are potentially detectable with current or near-future technology. We have simulated phase curve signatures in direct imaging of hypothetical starshades in systems targeted by the upcoming Habitable Worlds Observatory (HWO), which will be tasked with searching for Earth-like exoplanets orbiting nearby stars. The starshade is assumed to be a circular, reflecting surface placed at the inner Lagrange point between the star and the planet. Our results show that the phase curve of a starshade has a distinct shape compared to that of a typical planet. The phase-curve signature lies above the expected 1σ = 10−11 single-visit precision in contrast ratio of the telescope for 70.8 per cent of the target stars for the expected inner working angle (IWA) of around 60 mas. If the IWA can be reduced to 45 mas, the percentage of stars above the 1σ limit increases to 96.7 per cent. With a sufficiently small IWA, HWO should be able to detect anomalies in light curves caused by starshades or similar highly reflective surfaces – which could serve as key indicators for technologically advanced civilizations.
Keywords: extraterrestrial intelligence; exoplanets; planets and satellites: detection; stars: evolution; Earth and Planetary Astrophysics; Solar and Stellar Astrophysics